Inter-agency Collaboration for Graduate Employment Opportunities in Uganda: a Case for Investigating the Structure, Social Capital, and Agency of Organizations - Ntale, Peter Dithan (Journal of African American Studies, 2019)
Africa’s population has grown from 477 million in 1980 to 1.25 billion people by 2017. Whereas this is expected to double to 2.4 billion people by 2050, there is uncertainty over the continent’s preparedness to provide opportunities for its youthful population (Hilson and McQuilken, The Extractive Industries and Society 1:104–118, 2014). Efforts by different stakeholders to create employment opportunities have been largely unsuccessful. Rae (Journal of GeneralManagement, 40:79–95, 2014) attributes this failure to the autonomous and individualistic actions of different agencies in executing their mandates. In doing this, they compete and conflict against each other which discourages efforts towards job creation. Taking cognizance of this anomaly, this paper urges research into the structure, social capital, and agency of organizations with the view to suggest ways of promoting the kind and level of collaboration that is desired among the organizations. The paper starts with an introduction, the context of graduate unemployment in Uganda, discusses the efforts of different agencies, a bit of literature review, the theoretical underpinnings, knowledge gap, a case study and what Uganda’s organizations learn from the Urban Partnership Program, and finally the conclusion.
Keywords: Inter-agency collaboration; Graduates; Employment opportunities